A hybrid disassembly framework for disassembly of electric vehicle batteries. (12th January 2021) - Tan, Wei Jie; Chin, Christina Mei Mei; Garg, Akhil; Gao, Liang
Summary: In a recent study, it was determined that the usage of Li‐Ion batteries in electric vehicles (EVs) represent a huge portion of the overall usage. In order to foster a sustainable future, Li‐Ion batteries in EVs generally undergo a disassembly during the recycling process, which is intended for secondary purposes or recover useful materials and components. However, the current disassembly process is significantly time consuming and expensive. Hence in this research, a disassembly framework is presented, which focuses on improving the disassembly efficiency. The framework consists of a hybrid disassembly workstation that utilizes modified automated robotic arms and a specialized tool to allow an improvement in the disassembly time. The framework focuses on optimizing several identified parameters. These parameters (Design, Safety, and Cost) were identified through a comprehensive review and analysis of the schematics and properties of conventional EV battery packs along with the disassembly procedures being currently in practice. Additionally, the framework also consists of a conceptualized disassembly procedure developed based on the potential improvements of the hybrid disassembly. The framework proposed would allow a 5‐step reduction in the overall disassembly steps, and thus would be highly suited to be adopted in the EV disassembly industry. Abstract : Proposed hybrid disassembly workstation during the recycling of batteries.